2012
DOI: 10.1080/02607476.2012.656441
|View full text |Cite
|
Sign up to set email alerts
|

Supporting newly recruited teachers in a unique area, the Northwest Territories in Canada

Abstract: Formal and mandatory induction programmes have been widely implemented in many countries to support newly qualified teachers as they cope with the stress and professional demands of their first year in the profession of teaching. This article presents the results of a quantitative and qualitative research study which examined the context of a mandatory induction programme of four phases in a unique place, the Northwest Territories in Canada, where new (experienced) and beginning (inexperienced) teachers are re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…Canadian research documenting new teacher needs and the best ways to support them is still a developing field [4,46,51,52]. While any kind of support for beginning teachers is better than none [53], continuous reflection on existing support is key to improving its effectiveness [46,47]. What is known is that new teachers require support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Canadian research documenting new teacher needs and the best ways to support them is still a developing field [4,46,51,52]. While any kind of support for beginning teachers is better than none [53], continuous reflection on existing support is key to improving its effectiveness [46,47]. What is known is that new teachers require support.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is much evidence for the fact that support for beginning teachers across Canada is increasing, it remains that some of that support is inconsistently implemented [36,44,45]. Documenting existing induction support in order to improve its effectiveness represents an important part of improving support and its implementation [46,47]. Research on how new teachers are supported in their work towards improving student learning outcomes while strengthening their own teaching capabilities is needed.…”
Section: Professional Learning For New Teachersmentioning
confidence: 99%
“…Including in teacher effectiveness is preparation in both pedagogic and subject content, credentials, experience, and test scores (Rice 2003). Rass (2012) reported that induction programmes 'develop cultural competence to help the new teachers to deal successfully with the pupils and empower them in promoting multiculturalism' (141). In Indonesia, teacher professional development programmes and other forms of training have been conducted, but they are not yet considered to be effective in increasing teacher quality (Jalal et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…JET has previously published research into the difficulties that beginning teachers face when placed in remote rural locations (see for example, Cobbold 2006or Rass 2012 and Demet Seban's four-year longitudinal study provides another example of the issues raised by such challenging contexts. Seen through the lens of Gee's (2000) identity framework the data provided by her student teachers indicates that for students brought up in urban environments the experience of teaching in a rural school's multigrade classroom can be profound in challenging their assumptions about teaching and teacher identity.…”
mentioning
confidence: 97%